Animals, anthropomorphism and mediated encounters - Parkinson, Claire (Abingdon, Oxon ; New York, NY : Routledge, an imprint of the Taylor & Francis Group, 2020)
This book critically investigates the pervasiveness of anthropomorphised animals in popular culture. Anthropomorphism in popular visual media has long been denounced for being unsophisticated or emotionally manipulative. It is often criticised for over-expressing similarities between humans and other animals. This book focuses on everyday encounters with visual representations of anthropomorphised animals and considers how attributing other animals with humanlike qualities speaks to a complex set of power relations. Through a series of case studies, it explores how anthropomorphism is produced and circulated and proposes that it can serve to create both misunderstandings and empathetic connections between humans and other animals. This book will appeal to academics and students interested in visual media, animal studies, sociology and cultural studies.
OCLC-licensed vendor bibliographic record.
Keywords: Animal psychology; Anthropomorphism; Human-animal relationships; SCIENCE / Earth Sciences / Geography